Development of three phase load flow by reusing object oriented single phase load flow - Abdel-Akher, M.; Nor, K.M.; Mokhlis, Hazlie; Rashid, A.H.A. (IEEE, 2004)
This paper presents the development of three phase load flow software by reusing an existing single phase load flow software component. The single phase load flow component was developed using Object Oriented and Component Based Development methodologies. The object oriented power system model of the single phase load flow component was established separately from the mathematical solution. The proposed three phase load flow is formulated based on symmetrical components theory, which involves a positive sequence load flow solution. Based on this relation, the single phase load flow component and its power system model can be reused in the development of the three phase load flow software. The single phase load flow power system model is extended for tnodeling three phase devices such a5 untransposed lines, three phase loads ... etc. Reuse of the single phase component is achieved through composition relationship, where the positive sequence load flow is modeled as an object inside the three phase load flow component. The three phase load flow is solved by incorporating the solution of both positive sequence load flow and the nodal voltage equations for zero and negative sequence networks.